EFEKTIVITAS BELAJAR DARING SISWA SD BANDA ACEH-ACEH BESAR PADA MASA PANDEMI COVID 19 (PIONIR: JURNAL PENDIDIKAN, 2020)
At the end of 2019, the world was shocked by the emergence of a deadly virus; (Coronavirus Disease 19 (COVID 19). Since its emergence, the Indonesian government issued a policy set out in Government Regulation Number 21 of 2020 concerning Large Scale Social Restrictions. One of the policies is to stop learning activities at school, that is replaced by online learning at home. This regulation has been stated in the Ministry of Education and Culture Circular Letter number 15 of 2020; "the aim of implementing learning at home is to ensure the fulfillment of students' rights to get educational services during the Covid 19”. The This study, therefore, aimed to figure out the effectiveness of learning at the homes of elementary school students in the city of Banda Aceh and Aceh Besar during the Covid 19 pandemic and to analyze the respond of students’ elementary school parents toward the learning process conducted at home during the Covid 19 disease. This study is a qualitative approach using a survey method. The results of this study indicate that during online learning, teachers use the WhatsApp application more for learning, and less do video conferencing with students, however, some teachers still accompany students to learn online and also provide clear work instructions to students. Another result found that teachers experienced many obstacles, such as unstable internet networks, and th parents who did not understand children's learning materials, and more than 80% of elementary school teachers in Banda Aceh and Aceh Besar cities did not agree with the online learning process, due to the online learning more effective to be applied in elementary schools.
Keywords: E-Learning; Teacher